Synovial hemangioma: A rare benign synovial lesion - Rajni; Khanna Geetika; Gupta Anu; Gupta Vikas (Wolters Kluwer Medknow Publications, 2008)
We report an unusual case of a 10-year-old female with complaints of pain and swelling of the right knee for the last 4 years along with the limitation of movement for last 1 year. Repeated fine needle aspirations yielded blood and a provisional diagnosis of hemarthrosis was suggested. Coagulation profile subsequently carried out was found to be within normal limits. Arthroscopic biopsy was performed and tissue was sent for histopathological examination. A diagnosis of synovial hemangioma was made. Subtotal synovectomy was performed and the lesion was completely excised. The patient is completely asymptomatic and shows no signs of recurrence at 1 year.